دراسات ميدانية حول ذوي الاحتياجات الخاصة - موسى, علي (جامعة الوادي University of Eloued, 2018)
The difficulty of "developmental learning" or lack of the minimum ownership of the basic competencies in the basic stage of education; The variables are the results of the difficulty of learning and are considered the main cause, and represent these variables among the most important educational - educational issues are very important in Arab educational institutions because the negative repercussions on the pre-school, especially those who know learning difficulties, results in poor school achievement, behavior and poor adaptation to the school atmosphere, which makes the educational institution know the difficulty of discipline. We will present through this paper the reality of people with special needs in the Tunisian educational institution through their behavioraleducational assessment and their learning difficulties in the second stage of general public education.
صعوبات التّعلم بالمؤسّسة التّعليميّة التّونسيّة
مقال
Keywords: learning difficulty; academic achievement; schooling; basic competencies; behavior disorder; lateness; exclusion; dropouts; special need